Ion Impregnation Effect of Fe, Cu, Cr-attributed Mordenite on Stearic Acid Cracking - Abdulloh Abdulloh; Ulfa Rahmah; Satya Candra Wibawa Sakti; Alfa Akustia Widati; Ahmadi Jaya Permana; Rochadi Prasetya; Musbahu Adam Ahmad; Mochamad Zakki Fahmi (Universitas Gadjah Mada, 2022)
The improvement in the design of mordenite-based catalysts focuses on the present study to fulfill the massive demand for bio-aviation fuel (BAF) as renewable energy. Modification of the mordenite through ionic impregnation of Fe, Cu, and Cr, has supported the mordenite to perform with better efficiency and activity in catalyzing the cracking process of stearic acid. The adjustment on catalytic activity was carried out by simply reacting the catalyst with stearic acid at 190 °C and investigating cracking products with Gas Chromatography-Mass Spectroscopy. The results of the GC-MS test of the cracking product showed the formation of alkane-alkene and aromatic compounds. BAF was selectively obtained (30.27%) when the reaction was catalyzed by FeCuCr/mordenite catalyst. The BAF derived from FeCuCr/mordenite contained hydrocarbons that include xylene, mesitylene, dodecane, tridecane, tetradecane, and pentadecane. However, reduced selectivity was realized (19.85%) when the reaction was catalyzed by nano FeCuCr/mordenite. Its hydrocarbon constituents include benzene, tetradecane, and pentadecane compounds.